Understanding and Improving Consumer Reactions to Service Bots - Castelo, Noah; Boegershausen, Johannes; Hildebrand, Christian; Henkel, Alexander P (Journal of Consumer Research, 2023)
Abstract Many firms are beginning to replace customer service employees with bots, from humanoid service robots to digital chatbots. Using real human–bot interactions in lab and field settings, we study consumers’ evaluations of bot-provided service. We find that service evaluations are more negative when the service provider is a bot versus a human—even when the provided service is identical. This effect is explained by consumers’ belief that service automation is motivated by firm benefits (i.e., cutting costs) at the expense of customer benefits (such as service quality). The effect is eliminated when firms share the economic surplus derived from automation with consumers through price discounts. The effect is reversed when service bots provide unambiguously superior service to human employees—a scenario that may soon become reality. Consumers’ default reactions to service bots are therefore largely negative but can be equal to or better than reactions to human service providers if firms can demonstrate how automation benefits consumers.